‘We don’t talk about that around here’: an interpretative phenomenological analysis (IPA) of South Asian male survivors’ experiences of childhood sexual abuse in the UK - B. Kennath Widanaralalage; Stacey Jennings; Coral J. Dando; Jay-Marie Mackenzie (BMC Psychology)
Abstract Background Sexual violence against men is an understudied issue, particularly among ethnic minority groups. This study explored how South Asian cultural norms shape disclosure and help seeking for adult male survivors of childhood sexual abuse in the UK. Methods Using interpretative phenomenological analysis (IPA), semi-structured interviews were conducted with 11 South Asian male survivors of childhood sexual violence currently living in the UK. Participants were recruited through specialist support organisations. Interviews explored participants’ experiences of disclosure, cultural factors surrounding sexual violence, and barriers/facilitators to support. Data were analysed following IPA’s idiographic approach to identify themes across participant accounts. Results Three key themes were identified centred on familial honour and pressures, cultural taboos, and barriers to support/justice. Familial reputational pressures made survivors reluctant to disclose and they often received dismissive reactions. Cultural taboos about sex and mental health meant survivors felt unable to recognise their experiences and needs. Barriers to professional support included stigma and lack of cultural understanding. Distrust of systems discouraged justice-seeking, with negative experiences for those reporting abuse. Conclusions Traditional South Asian values regarding family honour, gender norms, and stigma created obstacles to disclosure and help seeking for male survivors. Culturally-tailored outreach and supports are needed to overcome taboos and empower South Asian male survivors to access appropriate care. Findings emphasise the intersection of masculinity and culture in shaping experiences of sexual violence. Further research should explore diversity within South Asian communities and experiences navigating systems and services.